ESTIMATION OF MAXIMUM EARTHQUAKE MAGNITUDE OF EARTHQUAKE POTENTIALS FOR YOGYAKARTA DEPRESSION AREA, INDONESIA - Myo Thant; Subagyo Pramumijoyo; Heru Hendrayana; Hiroshi Kawase; Agus Darmawan Adi (Journal of Applied Geology, 2015)
Maximum magnitudes of earthquake potentials are estimated for Yogyakarta depression area by using the faultlength and earthquake magnitude relations for fault specific seismic sources. For estimation of maximum earthquake magnitude, the fault specific seismic sources are modeled as 18 normal faults and 6 strike-slip faults sources referring the geological map of McDonald, 1984 and Rihardjo et al., 1995. For the present area the subduction zone earthquakes are expected to happen in the offshore region regarding the study on the seismicity of the region and the focal mechanisms of the past earthquakes. So three area sources are also assumed for this region and the possible maximum earthquake magnitudes for these sources are determined by probabilistic approaches.